Comparing the Effectiveness of Metacognitive Skills Training with Executive Function Skills Training on Biological Markers in Patients with Coronary Artery Disease - Davoodi, Marjaneh; Malihi Alzakerini, Saeid; Nikpajouh, Akbar; Sabet, Mehrdad (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Cardiovascular diseases are the primary cause of mortality in Iran. The current research aimed to compare the effectiveness of metacognitive skills training with executive function skills training on the biological markers of patients with coronary artery disease. Methods and Materials: This study was a quasi-experimental design with a pre-test, post-test, and follow-up alongside a control group. The population consisted of patients suffering from coronary artery disease, selected conveniently from those visiting a specialized cardiac clinic affiliated with a specialized and subspecialized hospital in Kish. Data were collected using the Beck Depression Inventory and the Wisconsin Card Sorting Test. The metacognitive skills training sessions were conducted using the Metacognitive Training package (D-MCT) and the executive functions training (the Calm Rehabilitation package), over 8 sessions of 90 minutes each week for the experimental group members. No intervention was performed for the control group. Data were analyzed using multivariate analysis of variance and SPSS software version 22. Findings: The results indicated that the executive function skills training (Calm Rehabilitation package) significantly affected blood sugar (P<0.01, F=23.44) and systolic blood pressure (P<0.01, F=19.82) compared to the control group. Similarly, metacognitive skills training (D-MCT package) significantly influenced blood sugar (P<0.01, F=85.40) and systolic blood pressure (P<0.01, F=22.13) in comparison to the control group. Conclusion: It can be concluded that both metacognitive and executive function skills training were effective on the biological markers of patients with coronary artery disease, but there was no difference between the two treatments on the biological markers of patients with coronary artery disease.